Perception of Iraqi Orthodontists and Patients toward Accelerated Orthodontics - Ali M. Al-Attar; Samher Al-Shaham; Mushriq Abid (International Journal of Dentistry)
Background/Purpose. In the literature, no consensus about the duration of orthodontic treatment has been reached out. This study aimed to identify orthodontist’s and patient’s perception about the time of orthodontic treatment and their willingness to undergo and pay for various acceleration techniques and procedures. Materials and Methods. An electronic survey was conducted from August to October 2020. The questionnaire consisted of 20 multiple choice questions which was designed and emailed to members of the Iraqi Orthodontic Society and self-administered to patients in several orthodontic centers in Baghdad. The questionnaire included questions about the perception toward the duration of orthodontic treatment, approval of different procedures used to reduce treatment time, and how much fee increment they are able to pay for various techniques and appliances. Descriptive and chi-square test statistics were used, and the level of significance was set at p≤0.05. Results. The response rate was 78.7%. The willingness for additional techniques and procedures was rated in the following order: customized appliances: 50.8% orthodontists and 38.4% patients, followed by intraoral vibrating devices: 49.2% orthodontists and 38.1% patients, piezocision: 10.2% orthodontists and 8.2% patients, and corticotomies: 8.1% orthodontists and 5.9% patients. Most orthodontists were willing to pay up to 40% of treatment income for the acceleration procedure, while the payment of patients was up to 20%. Conclusion. Both orthodontists and patients were interested in techniques that can decrease the treatment duration. Noninvasive accelerating procedures were more preferable by orthodontists and patients than invasive surgical procedures.